Ultralow-temperature super-tough low-carbon bainite weather-resistant bridge steel and preparation method thereof
Through a reasonable alloy design and TMCP process, the micro -organization structure of ultra -low temperature ultra -tough low -carbon Bechinoptera -weather bridge steel is adjusted, and the problem of difficulty in reaching multiple performance balance in low -temperature environment in low temperature environments has been solved. , Easy to weld, low temperature toughness, low cost, and corrosion resistance.
Patent Information
- Application Number
- CN202411574126.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
Existing weather-resistant bridge steels are difficult to achieve a balance between high strength, easy welding, low temperature toughness, low cost and corrosion resistance in low temperature environments, especially at lower temperatures, impact toughness is less studied.
Using ultra -low -temperature ultra -tough low -carbon Bechina tolerance bridge steel, through a reasonable alloy design and TMCP process, regulate the micro -tissue structure, form an ultra -fine crystal grain Bechones and trace residual Austeen tissue to improve the large angle crystal world Proportion and crystal boundaries.
It realizes high -strength, high toughness, and high corrosion resistance in ultra -low temperature environments, and reduces production costs, and meets the high performance needs of bridge steel in ultra -low temperature environments.
Smart Images

Figure CN119372554A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bridge steel manufacturing, and specifically relates to an ultra-low temperature, ultra-tough, low-carbon bainite weather-resistant bridge steel and a preparation method thereof. Background Art
[0002] With the rapid development of the global economy, the scale and complexity of building structures are increasing, and the demand for bridge steel with excellent comprehensive properties such as toughness, corrosion resistance and weldability is increasing. At present, the research on weather-resistant bridge steel is mainly focused on corrosion resistance, low-temperature toughness and high strength. However, the current weather-resistant bridge steel composition system is mainly based on the Cu-Cr-Ni system, which is difficult to meet the corrosion resistance requirements under higher salinity levels. It generally requires coating treatment, and the coating cost generally accounts for 12% of the initial construction cost, and it needs to be repainted every 6 to 12 years, which undoubtedly greatly increases the production cost; the research on low-temperature toughness is currently mainly aimed at the temperature level of -60℃, and there are few research results on impact toughness at lower temperatures; in the field of high strength, it is mainly through the addition of strengthening metal elements such as Nb, V, Ti and reasonable rolling and heat treatment processes, but this also greatly increases the production cost. In summary, it is difficult for weather-resistant bridge steel for low-temperature environments to achieve a balance between high strength, easy welding, low-temperature toughness, low cost and corrosion resistance. Therefore, it is of great significance to develop a weather-resistant bridge steel for low-temperature environments with multiple good properties.
[0003] The Chinese patent application with publication number CN 117448674 A discloses "a 550MPa weather-resistant bridge steel for plateau environment and its manufacturing method". The chemical composition and mass percentage of the steel plate are C: 0.05%~0.08%, Si: 0.2%~0.5%, Mn: 1.4%~1.8%, P: 0.08%~0.15%, S: ≤0.003%, Mo: 0.1%~0.3%, Cu: 0.1%~0.3%, Cr: 1.4%~1.8%, Nb: 0.03%~0 .05%, Ti: 0.008%~0.002%, Ni: 0.2%~0.4%, Al: 0.02%~0.04%, the rest is Fe and unavoidable impurities; the TMCP+ metastable quenching and tempering process is adopted, and the final product yield strength is ≥600MPa, tensile strength is 750~850MPa, elongation>20%, yield strength ratio<0.85, -40℃ impact energy ≥120J, and the thinning amount in the hundred-year life cycle under the typical Qinghai-Tibet plateau environment is <0.8mm. Its strength and corrosion resistance are good, but its high P content easily leads to the "cold brittleness" phenomenon, so that it can only meet the impact performance of -40℃, and it is difficult to meet the use requirements in ultra-low temperature environments.
[0004] The Chinese patent application with publication number CN 117305697 A discloses "a 9Ni steel plate and its manufacturing method", the chemical composition of which is: C: 0.04%~0.05%, Si: 0.15%~0.35%, Mn: 0.50%~0.80%, Ni: 8.5%~9.5%, P: ≤0.004%, S: ≤0.002%, Al: 0.015%~0.045%, the rest is Fe and unavoidable impurities; the microstructure is regulated by thermomechanical rolling combined with QT heat treatment process, and the final product performance is: yield strength ≥590MPa, tensile strength ≥690MPa, elongation ≥19%, yield strength ratio ≤0.9, -196℃ impact energy ≥100J. The steel has excellent low temperature toughness, but the high production cost represented by the high Ni content determines that it cannot be used on a large scale in bridge steel.
[0005] The Chinese patent application with publication number CN 116637931 A discloses "a rolling method for high-toughness high-manganese austenitic low-temperature steel plate". The chemical composition of the steel plate is: C: 0.41%~0.50%, Si: 0.20%~0.27%, Mn: 22.5%~25%, Cu: 0.41%~0.50%, V: 0.02%~0.05%, Cr: 3.2%~4.0%, Nb: 0.011%~0.015%, P: ≤0.010%, S: ≤0.0014%, Al: 0.015%~0.045%, and the rest is Fe and unavoidable impurities; the mechanical properties finally obtained by hot rolling and quenching process are: yield strength: 402~442MPa, tensile strength: 802~832MPa, elongation: 57%~64%, -196℃ impact energy ≥203J. The steel exhibits excellent low-temperature toughness, but its strength is low. In addition, its high alloy content of more than 25% and austenite structure increase the difficulty of welding, which has limitations for bridge steel.
[0006] In summary, most existing steel grades only meet one or several performance requirements and cannot meet the requirements of high strength, easy welding, low temperature toughness, low cost, and corrosion resistance. It is of great significance for the construction of bridge construction projects to obtain a good match of the above properties by regulating the microstructure through reasonable alloying methods and TMCP technology. Summary of the invention
[0007] The invention belongs to the technical field of bridge steel manufacturing, and specifically relates to an ultra-low temperature, ultra-tough, low-carbon bainite weather-resistant bridge steel and a preparation method thereof.
[0008] The technical solution of the present invention is: The invention discloses an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel, whose chemical composition and weight percentage content are C: 0.04%-0.08%, Si: 0.20%-0.50%, Mn: 0.50%-1.0%, P: ≤0.015%, S: ≤0.003%, Al: 0.020%-0.030%, Ni: 0.80%-1.50%, Cu: 0.30%-0.50%, Mo: 0.40%-0.70%, and the balance is Fe and other inevitable impurities.
[0009] The carbon element is the most important element that determines the mechanical properties of steel. As the carbon content increases, the strength and hardness of the steel will increase significantly, but too high a carbon content will aggravate the lattice distortion and reduce the plasticity and toughness. In addition, steel with a high carbon content is prone to produce hardened structures during welding, which reduces the weldability of the steel. Therefore, the carbon content should not be too high. The present invention adopts a low carbon content component design of 0.04% to 0.08%.
[0010] Si can significantly improve the strength and hardness of steel, but when the content exceeds 3%, it will damage the plasticity and toughness of steel. Si is easy to form oxide inclusions, which affects the quality of welds and deteriorates the weldability of steel. Si can also increase the proportion of α-FeOOH and refine it, significantly reducing the corrosion rate. Therefore, the mass percentage range of Si element in this composition design is controlled at 0.20% to 0.50%.
[0011] The Mn element can be dissolved in ferrite and austenite to form solid solution strengthening, improve the strength and hardness of steel, and maintain good ductility. In addition, Mn can improve the hardenability of steel, and a deeper hardened layer can be obtained during the quenching process, thereby improving the hardness and wear resistance of steel. However, the Mn element has a deteriorating effect on corrosion performance. Considering comprehensively, the present invention adopts a low Mn content composition design of 0.5% to 1.0%.
[0012] The P element alone has no significant effect on the formation of a protective rust layer, but its synergistic effect with Cu can significantly improve corrosion resistance. The higher the P content, the less mass loss of the steel. However, too high a P content will cause brittle fracture of the steel when subjected to vibration or impact, so this composition design strictly controls the P content within 0.015%.
[0013] Ni is an austenite-forming element, which can significantly improve the low-temperature toughness of steel. In addition, Ni is also recognized as one of the most effective corrosion-resistant elements, which can significantly improve the corrosion resistance by increasing the self-corrosion potential, promoting the formation of α-FeOOH, increasing the density of the rust layer, and changing the ion selectivity of the rust layer. Therefore, the mass percentage content of Ni in this composition design is controlled within the range of 0.80% to 1.50%.
[0014] Cu is the first element found to effectively improve the corrosion resistance of steel. It can induce anodic passivation of steel to reduce the corrosion rate and improve the compactness of the rust layer. However, during the rolling process, the surface of the steel will be copper-rich, resulting in thermal embrittlement. However, Ni can minimize this phenomenon. Therefore, a certain amount of Cu and Ni are generally added in the composition design of high-strength weathering steel to ensure toughness and corrosion resistance. The mass percentage range of the Cu element of the present invention is controlled to be 0.30% to 0.50%.
[0015] Mo can form a strengthening phase with Fe, improve the continuity of the grain boundary interface of steel, and increase the shear strength of the grain boundary equilibrium interface, thereby significantly enhancing the hardness and strength of steel. Mo can also improve hardenability and thermal strength. In addition, Mo can significantly improve pitting resistance, while promoting the aggregation of insoluble salts in the inner stable rust layer, improving density and inhibiting the corrosive anion Cl - The content of Mo element by mass percentage is controlled within the range of 0.40% to 0.70%.
[0016] Furthermore, the above-mentioned ultra-low temperature ultra-tough low-carbon bainitic weathering bridge steel, the corrosion resistance index I value of the ultra-low temperature ultra-tough high-strength weathering bridge steel is ≥6.5.
[0017] Furthermore, the above-mentioned ultra-low temperature, ultra-tough, low-carbon bainitic weathering bridge steel uses the TMCP process to regulate the microstructure to obtain ultrafine-grained bainite and trace residual austenite structure. In the characteristic distribution of grain boundaries of the structure, the grain size is ≤6μm, and the proportion of large-angle grain boundaries is ≥50%.
[0018] Furthermore, the above-mentioned ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel has a yield strength of 480-550MPa, a tensile strength of 620-690MPa, an elongation after fracture A≥20%, and an average impact energy A at -130°C. kv >160J.
[0019] Furthermore, the above-mentioned ultra-low temperature ultra-tough low-carbon bainitic weathering bridge steel has a minimum thickness of 20 mm, a maximum thickness of 80 mm, and a compression ratio of ≥6 during the rolling process.
[0020] The above-mentioned method for preparing ultra-low temperature, ultra-tough, high-strength and weather-resistant bridge steel comprises a preparation process including smelting, continuous casting, heating, rough rolling, finish rolling and water cooling, wherein: In the continuous casting process, during the heating process of the ingot, the heating temperature is 1180~1200℃, and the heating coefficient is 8~10min / cm. If the heating temperature is too high, the longer the holding time, the coarser the austenite grains, which has a great impact on the fine grain strengthening effect; if the heating temperature is too low, the carbides of the microalloying elements in the steel cannot be completely dissolved and their strengthening effect cannot be fully exerted.
[0021] In the rolling process, a two-stage controlled rolling process is adopted. The first stage is the rough rolling stage. The final rolling temperature is 1050~1090℃. A multi-pass reduction process is adopted. The reduction rate of a single pass is not less than 15% except for the widening pass. A large number of dislocations will be generated in the large deformation process of rough rolling, and then transformed into more stable boundaries, forming smaller grains and subgrains. The subgrains form small-angle grain boundaries during rotation and growth. As the subgrains continue to rotate, dislocations will dissociate and recombine, and transform into twins through the recovery twinning process. Recovery twinning can promote the occurrence of twin-induced continuous dynamic recrystallization, so that twins are transformed into high-angle grain boundaries, increasing the proportion of high-angle grain boundaries. The grain boundary energy will increase with the increase of the orientation error between adjacent grains, and reach the maximum value when the orientation error is 15°. Therefore, the high-angle grain boundary with an orientation error of more than 15° has a more obvious hindering effect on crack propagation. When encountering a crack, it will exert a distortion effect on it to hinder its propagation, which has a significant effect on improving toughness. In addition, a higher proportion of high-angle grain boundaries corresponds to fewer low-angle grain boundaries, which indicates that there are fewer substructures inside the grains. The ability of internal obstacles to hinder crack propagation is reduced, making it easier for cracks to propagate within the grains. The cracks have a smaller tendency to pass through grain boundaries. Therefore, for ultrafine-grained structures, the impact toughness can be significantly improved.
[0022] Finishing rolling is the final rolling temperature of the austenite non-recrystallization zone at 780~820℃, and the cumulative reduction rate is ≥60%. Finishing rolling needs to avoid the recrystallization zone. During the rolling process at a lower temperature, only the austenite grains are deformed, and evenly distributed dislocations are generated inside the grains, providing nucleation points for the subsequent ferrite phase transformation to obtain smaller grains. Smaller grain size means more grain boundaries. For fine grains, grain boundaries will hinder the cracks from growing to the critical size required for unstable propagation.
[0023] During the cooling process, the steel plate is sprayed with water to cool to 530-560℃ after rolling, with a cooling rate of 15-25℃ / s; then air-cooled to room temperature. Granular bainite mainly nucleates at the austenite grain boundary, and becomes ferrite sheets as carbon diffuses into the surrounding austenite. As carbon is enriched in austenite, the sheets gradually connect into blocks, surrounding smaller and smaller austenites to form islands. The block-like characteristics of granular bainite enhance the coordinated deformation of the strain gradient between adjacent grains, promote the tortuosity of the crack propagation path, thereby consuming more energy during the crack propagation process and significantly improving the impact toughness. After controlled rolling, austenite is rapidly cooled to the temperature range of the granular bainite phase transformation, making the phase transformation structure more refined, preventing or delaying the premature precipitation of carbides during the cooling process, making them dispersed and precipitated in the structure, and improving the strength. In addition, the slow cooling process after rapid cooling to the bainite transformation temperature will promote the redistribution of carbon atoms trapped in structural defects or dislocations, inhibiting the formation of large-sized granular bainite islands.
[0024] Advantages and beneficial effects of the present invention: 1. Based on reasonable alloying design, the present invention obtains ultrafine granular bainite structure through TMCP process. The granular bainite conforms to the one-dimensional growth model during nucleation and growth, and presents a bag-shaped boundary, which has a good barrier effect on the expansion of cracks. The small grain size and large-angle grain boundary improve the toughness. The ultra-low temperature toughness and corrosion resistance of the steel plate are improved while maintaining high strength. Under the premise of meeting the service requirements of high strength, high toughness and high corrosion resistance of bridge steel in ultra-low temperature environment, the production cost is greatly reduced.
[0025] 2. The low-temperature toughness of the ultra-low-temperature ultra-tough low-carbon bainitic weathering bridge steel involved in the present invention does not rely on the (residual) austenite in traditional low-temperature steels. The TMCP process is used to refine the grain size, increase the proportion of large-angle grain boundaries and alleviate stress concentration. Smaller grain size means more grain boundaries. For fine grains, grain boundaries will hinder the growth of cracks to the critical size required for unstable propagation; large-angle grain boundaries with high grain boundary energy will exert a twisting effect on cracks when encountering cracks to hinder their expansion. Low-carbon bainitic weathering bridge steel with these characteristics exhibits super toughness at ultra-low temperatures, can meet the low-temperature and high fracture toughness service requirements of high-strength weathering bridge steel in ultra-low temperature environments, avoid low-temperature fracture accidents of steel bridges, and conform to the development trend of long-life bridge steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The microstructure morphology of the steel plate of Example 1; Figure 2 The distribution of grain boundaries in the steel plate structure of Example 1; Figure 3 is the proportion of large and small angles in the steel plate structure of Example 1; Figure 4 The microstructure morphology of the finished steel plate of Example 2; Figure 5 The distribution of grain boundaries in the steel plate structure of Example 2; Figure 6 is the proportion of large and small angles in the steel plate structure of Example 2; Figure 7 The microstructure morphology of the finished steel plate of Example 3; Figure 8 The distribution of grain boundaries in the steel plate structure of Example 3; Fig. 9 It is the proportion of large and small angles in the steel plate structure of Example 3. DETAILED DESCRIPTION
[0027] In order to better understand the scheme and advantages of the present invention, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples of the specification. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention. Example 1
[0028] The chemical composition of an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel in this embodiment is as follows by weight: C: 0.05%, Si: 0.35%, Mn: 0.69%, P: 0.004%, S: 0.002%, Al: 0.024%, Ni: 1.01%, Cu: 0.40%, Mo: 0.61%, and the rest is Fe and unavoidable impurities. The preparation method includes smelting, continuous casting, heating, rough rolling, finish rolling, and cooling, wherein: During the heating process of the ingot, the ingot thickness was 250 mm, the heating temperature was 1200 °C, and the heating coefficient was 9 min / cm; The rough rolling end temperature is 1090°C, and the reduction ratios of each pass in the rough rolling stage are 9.14%, 15.54%, 18.76%, 21.58%, and 24.42% respectively; The finishing temperature of the finishing rolling is 797℃, the cumulative reduction rate is 67.53%; the final thickness is 30mm, and the compression ratio is 8.3; The water cooling rate is 17.8℃ / s, the final cooling temperature is 557℃, and then it is air-cooled to room temperature.
[0029] The corrosion resistance index I value of the ultra-low temperature, ultra-tough, high-strength and weather-resistant bridge steel plate prepared in this embodiment is 6.58. Figure 1 As shown in FIG. 1 , the ultra-low temperature, ultra-tough, high-strength, weather-resistant bridge steel plate produced by the method has a granular bainite structure with an average grain size of 3.7 μm. Figure 2 and Figure 3 As shown in the grain boundary distribution diagram, the proportion of large-angle grain boundaries (15~65°) is 70.1%.
[0030] Mechanical properties of the finished steel plate of this embodiment: The yield strength is 522MPa, the tensile strength is 660MPa, the elongation after fracture is 22.4%, the yield strength ratio is 0.79, and the impact energy at -130℃ is 170J. Example 2
[0031] The chemical composition of an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel in this embodiment is as follows by weight: C: 0.05%, Si: 0.35%, Mn: 0.69%, P: 0.004%, S: 0.002%, Al: 0.024%, Ni: 1.01%, Cu: 0.40%, Mo: 0.61%, and the rest is Fe and unavoidable impurities. The preparation method includes smelting, continuous casting, heating, rough rolling, finish rolling, and cooling, wherein: During the heating process of the ingot, the ingot thickness was 300 mm, the heating temperature was 1200 °C, and the heating coefficient was 9 min / cm; The rough rolling end temperature is 1050°C, and the reduction ratios of each pass in the rough rolling stage are 9.14%, 15.69%, 16.77%, 19.54%, and 24.95% respectively; The final rolling temperature is 809℃, the cumulative reduction rate in the finishing rolling stage is 65.23%; the final thickness is 40mm, and the compression ratio is 7.5; The water cooling rate is 17.3℃ / s, the final cooling temperature is 554℃, and then it is air-cooled to room temperature.
[0032] The corrosion resistance index I value of the ultra-low temperature, ultra-tough, high-strength and weather-resistant bridge steel plate prepared in this embodiment is 6.58. Figure 4 As shown in FIG. 1 , the ultra-low temperature, ultra-tough, high-strength, weather-resistant bridge steel plate produced by the method has a granular bainite structure with an average grain size of 5.9 μm. Figure 5 and Figure 6 As shown in the grain boundary distribution diagram, the proportion of large-angle grain boundaries (15~65°) is 51.2%.
[0033] Mechanical properties of the finished steel plate of this embodiment: The yield strength is 483MPa, the tensile strength is 623MPa, the elongation after fracture is 25.4%, the yield strength ratio is 0.78, and the impact energy at -130℃ is 168J. Example 3
[0034] The chemical composition of an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel in this embodiment is as follows by weight: C: 0.05%, Si: 0.35%, Mn: 0.69%, P: 0.004%, S: 0.002%, Al: 0.024%, Ni: 1.01%, Cu: 0.40%, Mo: 0.61%, and the rest is Fe and unavoidable impurities. The preparation method thereof includes smelting, continuous casting, heating, rough rolling, finish rolling, and cooling, wherein: During the heating process of the ingot, the ingot thickness was 320 mm, the heating temperature was 1200 °C, and the heating coefficient was 9 min / cm; The rough rolling end temperature is 1075°C, and the reduction ratios of each pass in the rough rolling stage are 9.87%, 15.23%, 16.79%, 20.79%, and 24.35% respectively; The final rolling temperature is 815℃, the cumulative reduction rate in the finishing rolling stage is 63.09%; the final thickness is 45mm, and the compression ratio is 7.1; The water cooling rate was 20.5°C / s, the final cooling temperature was 545°C, and then air-cooled to room temperature.
[0035] The corrosion resistance index I value of the ultra-low temperature, ultra-tough, high-strength and weather-resistant bridge steel plate prepared in this embodiment is 6.58. Figure 7 As shown in FIG. 1 , the ultra-low temperature, ultra-tough, high-strength, weather-resistant bridge steel plate produced by the method has a granular bainite structure with an average grain size of 5.3 μm. Figure 8 and Fig. 9 As shown in the grain boundary distribution diagram, the proportion of large-angle grain boundaries (15~65°) is 52.0%.
[0036] Mechanical properties of the finished steel plate of this embodiment: The yield strength is 504MPa, the tensile strength is 641MPa, the elongation after fracture is 24.6%, the yield strength ratio is 0.79, and the impact energy at -130℃ is 182J. Example 4
[0037] The chemical composition of an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel in this embodiment is as follows by weight: C: 0.05%, Si: 0.35%, Mn: 0.68%, P: 0.005%, S: 0.002%, Al: 0.027%, Ni: 1.41%, Cu: 0.42%, Mo: 0.69%, and the rest is Fe and unavoidable impurities. The preparation method thereof includes smelting, continuous casting, heating, rough rolling, finish rolling, and cooling, wherein: During the heating process of the ingot, the ingot thickness was 400 mm, the heating temperature was 1200 °C, and the heating coefficient was 9 min / cm; The rough rolling end temperature is 1059°C, and the reduction ratios of each pass in the rough rolling stage are 8.68%, 15.77%, 17.83%, 20.01%, and 23.17% respectively; The final rolling temperature is 818℃, the cumulative reduction rate in the finishing rolling stage is 61.38%; the final thickness is 60mm, and the compression ratio is 6.7; The water cooling rate was 21.11°C / s, the final cooling temperature was 558°C, and then it was air-cooled to room temperature.
[0038] The ultra-low temperature, ultra-tough, high-strength and weather-resistant bridge steel plate produced by this method has a corrosion resistance index I value of 6.73, a granular bainite structure, an average grain size of 4.2 μm, and a large-angle grain boundary (15-65°) accounting for 62.7%.
[0039] Mechanical properties of the finished steel plate of this embodiment: The yield strength is 516MPa, the tensile strength is 662MPa, the elongation after fracture is 20.8%, the yield strength ratio is 0.78, and the impact energy at -130℃ is 174J. Example 5
[0040] The chemical composition of an ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel in this embodiment is as follows by weight percentage: C: 0.06%, Si: 0.34%, Mn: 0.70%, P: 0.006%, S: 0.003%, Al: 0.022%, Ni: 1.33%, Cu: 0.38%, Mo: 0.51%, and the rest is Fe and unavoidable impurities. The preparation method thereof includes smelting, continuous casting, heating, rough rolling, finish rolling, and cooling, wherein: During the heating process of the ingot, the thickness of the ingot is 300 mm, the heating temperature is 1200 °C, and the heating coefficient is 9 min / cm; The rough rolling end temperature is 1066°C, and the reduction ratios of each pass in the rough rolling stage are 9.24%, 15.83%, 17.24%, 19.16%, and 24.69% respectively; The final rolling temperature is 782℃, the cumulative reduction rate in the finishing rolling stage is 61.03%; the final thickness is 45mm, and the compression ratio is 6.7; The water cooling rate was 17.6°C / s, the final cooling temperature was 531°C, and then it was air-cooled to room temperature.
[0041] The ultra-low temperature, ultra-tough, high-strength, weather-resistant bridge steel plate produced by this method has a corrosion resistance index I value of 7.08, a granular bainite structure, an average grain size of 5.0 μm, and a large-angle grain boundary (15-65°) accounting for 53.8%.
[0042] Mechanical properties of the finished steel plate of this embodiment: The yield strength is 515MPa, the tensile strength is 650MPa, the elongation after fracture is 22.9%, the yield strength ratio is 0.79, and the impact energy at -130℃ is 178J.
[0043] The above are only some embodiments, which are only for better explanation of the present invention, not for limitation. A person skilled in the art may modify some technical features of the above embodiments, but any modification made within the principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An ultra-low temperature, ultra-tough, low-carbon bainite weathering bridge steel, characterized in that: The chemical composition and weight percentage are as follows: C: 0.04%~0.08%, Si: 0.20%~0.50%, Mn: 0.50%~1.0%, P: ≤0.015%, S: ≤0.003%, Al: 0.020~0.030%, Ni: 0.80%~1.50%, Cu: 0.30%~0.50%, Mo: 0.40%~0.70%, and the balance is Fe and other inevitable impurities.
2. The ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to claim 1, characterized in that: The corrosion resistance index I value of the ultra-low temperature and ultra-tough low-carbon bainitic weather-resistant bridge steel is ≥6.
5.
3. The ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to claim 1, characterized in that: The microstructure is regulated by the TMCP process to obtain ultrafine granular bainite and trace retained austenite.
4. The ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to claim 1, characterized in that: The ultra-low temperature ultra-tough low carbon bainite weathering bridge steel has a yield strength of 480-550 MPa, a tensile strength of 620-690 MPa, a yield strength ratio of <0.85, an elongation after fracture A≥20%, and an average impact energy A at -130°C. kv >160J.
5. The ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to claim 1, characterized in that: In the distribution of grain boundary characteristics of the organization, the grain size is ≤6μm and the proportion of large-angle grain boundaries is ≥50%.
6. The ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to claim 1, characterized in that: The minimum thickness of the ultra-low temperature and ultra-tough low-carbon bainite weather-resistant bridge steel is 20 mm, the maximum thickness is 80 mm, and the compression ratio of the rolling process is ≥6.
7. The method for preparing the ultra-low temperature ultra-tough low-carbon bainite weathering bridge steel according to any one of claims 1 to 6, characterized in that: The preparation process includes smelting, continuous casting, heating, rough rolling, finishing rolling and water cooling, among which: (1) In the continuous casting process, during the heating process of the ingot, the heating temperature is 1180-1200°C, and the heating coefficient is 8-10min / cm; (2) In the rolling process, a two-stage controlled rolling process is adopted. The first stage is the rough rolling stage, the final rolling temperature is 1050~1090℃, and the single pass reduction rate is not less than 15% except for the widening pass; the second stage is the finishing rolling stage, the final rolling temperature is 780~820℃, and the cumulative reduction rate in the finishing rolling stage is ≥60%; (3) In the cooling process, the steel plate is water-cooled to 530-560°C after rolling at a cooling rate of 15-25°C / s; and then air-cooled to room temperature.
Citation Information
Patent Citations
Rolling method of high-toughness high-manganese austenite low-temperature steel plate
CN116637931A
9Ni steel plate and preparation method thereof
CN117305697A
550MPa-grade weather-proof bridge steel for plateau environment and manufacturing method of 550MPa-grade weather-proof bridge steel
CN117448674A